The role of virtual leadership efficacy in cross-functional collaboration - Bizilj, Sanja (Psihološka obzorja (Ljubljana), 2025)
Virtual leadership requires creating a motivational environment for employees from diverse cultural and geographical backgrounds while promoting effective cross-functional collaboration throughout the organization. Despite the literature highlighting cross-functional collaboration as a key factor for success, there is a lack of research examining the relationship between virtual leadership and cross-functional collaboration. Our empirical study addresses this gap and explores the connection between factors such as the quality and frequency of leader-subordinate communication, a leader’s networking skills and virtual leadership efficacy, and the association between virtual leadership efficacy and cross-functional collaboration. We tested research hypotheses on a sample of 133 participants in a global company with a matrix structure. Using partial least squares structural equation modelling (PLS-SEM), we analysed the conceptual model and confirmed a positive relationship between communication quality, leader networking ability, and perceived virtual leadership efficacy. The research findings indicated that the frequency of communication between leader and subordinate does not have a significant impact on the perception of virtual leadership efficacy. The study also revealed the direct and indirect effects of virtual leadership efficacy on cross-functional collaboration. These findings contribute to a deeper understanding of the impacts of virtual leadership efficacy and broaden the understanding of the direct and indirect effects of virtual leadership efficacy on cross-functional collaboration.
Keywords: communication; cross-functional collaboration; komunikacija; matrična organizacijska struktura; matrix organizational structure; medfunkcijsko sodelovanje; mreženje; networking; virtual leadership; vodenje na daljavo